Pengaruh Kreativitas Ilustrator Pada Akun Instagram @qomikin Terhadap Minat Berdakwah Mahasiswa Komunikasi Dan Penyiaran Islam Universitas Ibn Khaldun Bogor Angkatan Tahun 2019 - Wildan, Muhammad; Fahmi Irfani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Illustration creativity has a very important role in conveying da'wah messages. The person who preaches must have an interest in illustrating so that in the future his preaching can be accepted, interesting, more effective and efficient. The aim of this research is to find out how the creativity of the illustrator on the @qomikin Instagram account influences the interest in preaching of Islamic Communication and Broadcasting students at Ibn Khaldun University, Bogor, class of 2019. Data was collected using a digital Google Form questionnaire instrument totaling 30 statements which were declared valid. based on the results of the validity test with the smallest r value of 0.300 > 0.207 (r table). Based on the results of the reliability test, it is known that the Cronbach's Alpha value of 0.945 > 0.6 is declared reliable. The results of the normality test using the Kolmogorov Smirnov test obtained a significance value of 0.200 > 0.05 so it can be said that the residual values ​​of variables X and Y are normally distributed. In the homogeneity test, results were obtained with a Sig value. 0.827 is greater than 0.05, then the variance of the population is the same or homogeneous. The results of the simple linear regression test in the Output Coefficients table above, in the Sig column. obtained a significance value of 0.000 < 0.05, so it can be said that H0 is rejected and Ha is accepted, which means that there is an influence of the creativity of the illustrator on the @qomikin Instagram account on the interest in preaching of Islamic Communication and Broadcasting students at Ibn Khaldun University, Bogor, Class of 2019. So it can be concluded that The creativity of the illustrator on the Instagram account @qomikin has an influence on the interest in preaching of Islamic Communication and Broadcasting students at Ibn Khaldun University, Bogor, Class of 2019.